2005
DOI: 10.1093/jmedent/42.1.57
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Potential of North American Mosquitoes (Diptera: Culicidae) to Transmit West Nile Virus

Abstract: Since Þrst discovered in the New York City area in 1999, West Nile virus (WNV) has become established over much of the continental United States and has been responsible for Ͼ10,000 cases of severe disease and 400 human fatalities, as well as thousands of fatal infections in horses. To develop appropriate surveillance and control strategies, the identiÞcation of which mosquito species are competent vectors and how various factors inßuence their ability to transmit this virus must be determined. Therefore, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
358
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(375 citation statements)
references
References 27 publications
1
358
1
7
Order By: Relevance
“…Although, this species is basically ornithophilic, it is also an opportunistic feeder that feeds readily on mammals including humans in residential areas. This species is regarded as an important vector for WNV (Molaei et al, 2007;Turell et al, 2005), and we suggest it is a candidate bridge vector for WNV in the Ryukyus. Culex ryukyensis of subgenus Culiciomyia fed on mammals (human and wild boar) and a reptile (lizard) in this study.…”
Section: D>h8jhh>dcmentioning
confidence: 88%
“…Although, this species is basically ornithophilic, it is also an opportunistic feeder that feeds readily on mammals including humans in residential areas. This species is regarded as an important vector for WNV (Molaei et al, 2007;Turell et al, 2005), and we suggest it is a candidate bridge vector for WNV in the Ryukyus. Culex ryukyensis of subgenus Culiciomyia fed on mammals (human and wild boar) and a reptile (lizard) in this study.…”
Section: D>h8jhh>dcmentioning
confidence: 88%
“…Culex pipiens L.-culex restuans theobald mosquitoes are the two primary WNv vectors in North America. The two species, which prefer water habitats with high organic content for their development cycle (Hilker and Westerhoff 2007;Turell and Dohm 2005), are morphologically the same (DeGaetano 2005). Owing to such similarity, the mosquito surveillance data for the Peel region lumps the two species together (it should be recalled that the model developed in the current study does not also distinguish between the two culex species).…”
Section: Study Area and Mosquito Speciesmentioning
confidence: 94%
“…Statistical study by Hilker and Westerhoff (2007) showed that hatching of the culex mosquito eggs varies during the year; being low in the winter (whenever the temperature is less than 10 • C) and high in the summer (whenever the temperature is in the range (22−30) • C). Rainfall can induce positive (where rainfall increases the availability of breeding sites for female culex mosquitoes to lay their eggs) or negative (excessive rainfall increases the mortality of immature mosquitoes) effect on culex dynamics (Turell and Dohm 2005).…”
Section: Temperature-and Rainfall-dependent Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…pipiens form molestus Forskal and Cx. quiquefasciatus Say, are competent vectors of WNV (Turell et al, 2002(Turell et al, , 2005 and WNV has been isolated frequently from Culex pipiens complex (Anderson et al, 1999;Bernard et al, 2001). Although WNV activity was not detected in eld-collected mosquitoes from our survey during 2003 2006 in Japan, it is also important to know which subspecies of the Culex complex are potential bridge vectors in the urban environment of Japan.…”
mentioning
confidence: 81%